Teaching the Rational Use of Medicines to medical students: a qualitative research - Patricio, Karina Pavão [UNESP]; Borges Alves, Nycholas Adriano [UNESP]; Arenales, Nadja Guazzi [UNESP]; Queluz, Thais Helena Abrahão Thomaz [UNESP] (Biomed Central Ltd., 2012)
Background: Prescribing is a complex and challenging task that must be part of a logical deductive process based on accurate and objective information and not an automated action, without critical thinking or a response to commercial pressure. The objectives of this study were 1) develop and implement a discipline based on the WHO's Guide to Good Prescribing; 2) evaluate the course acceptance by students; 3) assess the impact that the Rational Use of Medicines (RUM) knowledge had on the students habits of prescribing medication in the University Hospital.Methods: In 2003, the RUM principal, based in the WHO's Guide to Good Prescribing, was included in the official curriculum of the Botucatu School of Medicine, Brazil, to be taught over a total of 24 hours to students in the 4th year. We analyzed the students' feedback forms about content and teaching methodology filled out immediately after the end of the discipline from 2003 to 2010. In 2010, the use of RUM by past students in their medical practice was assessed through a qualitative approach by a questionnaire with closed-ended rank scaling questions distributed at random and a single semistructured interview for content analysis.Results: The discipline teaches future prescribers to use a logical deductive process, based on accurate and objective information, to adopt strict criteria (efficacy, safety, convenience and cost) on selecting drugs and to write a complete prescription. At the end of it, most students considered the discipline very good due to the opportunity to reflect on different actions involved in the prescribing process and liked the teaching methodology. However, former students report that although they are aware of the RUM concepts they cannot regularly use this knowledge in their daily practice because they are not stimulated or even allowed to do so by neither older residents nor senior medical staff.Conclusions: This discipline is useful to teach RUM to medical students who become aware of the importance of this subject, but the assimilation of the RUM principles in the institution seems to be a long-term process which requires the involvement of a greater number of the academic members.
Keywords: Rational Use of Medicines; Education; Medical; Undergraduate; Prescribing; Prescription; Drug